2017
DOI: 10.1186/s12881-017-0469-5
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study indicate role of preferentially transmitted monoamine oxidase gene variants in behavioral problems of male ADHD probands

Abstract: BackgroundAttention deficit hyperactivity disorder (ADHD) is an etiologically complex childhood onset neurobehavioral disorder characterized by age-inappropriate inattention, hyperactivity, and impulsivity. Symptom severity varies widely and boys are diagnosed more frequently than girls. ADHD probands were reported to have abnormal transmissions of dopamine, serotonin, and/or noradrenaline. Monoamine oxidase A (MAOA) and B (MAOB), mitochondrial outer membrane bound two isoenzymes, mediate degradation of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Previous studies have reported that ADHD pathogenesis may be associated with dysregulation of neurotransmitters such as dopamine, serotonin (5-hydroxytryptamine, 5-HT), and norepinephrine (Magula et al, 2019;Stewart et al, 2019;Suzuki et al, 2019). Others have shown that the incidence of ADHD may have a certain degree of heritability, and genes related to dopamine, norepinephrine, and 5-HT transmission have been found to be abnormally expressed in children with ADHD (Banerjee and Nandagopal, 2015;Karmakar et al, 2017;Kim et al, 2018). Although various theories have been proposed, the pathogenetic mechanisms underlying ADHD have not been fully clarified, which limits the development of new treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that ADHD pathogenesis may be associated with dysregulation of neurotransmitters such as dopamine, serotonin (5-hydroxytryptamine, 5-HT), and norepinephrine (Magula et al, 2019;Stewart et al, 2019;Suzuki et al, 2019). Others have shown that the incidence of ADHD may have a certain degree of heritability, and genes related to dopamine, norepinephrine, and 5-HT transmission have been found to be abnormally expressed in children with ADHD (Banerjee and Nandagopal, 2015;Karmakar et al, 2017;Kim et al, 2018). Although various theories have been proposed, the pathogenetic mechanisms underlying ADHD have not been fully clarified, which limits the development of new treatments.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Growing reports disclosed that miR-522 is nor- MAOB and MAOA have dramatic influence in the etiology of many neurological diseases. 18,19 Moreover, Liao et al 30 have proved that MAOA was involved in the development of adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Monoamine oxidase B (MAOB) is well known as a member of monoamine oxidase family that affects the etiology of many neurological diseases . The MAOB enzyme is located in the outer of mitochondrial membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Karmakar et al (2017) found that the MAOA gene rs6323 polymorphism was associated with behavioral problems in ADHD males in the Indian population [25]. These polymorphisms (uVNTR and rs6323) are known to be functional and affect the activities of MAOA enzymes [26,27].…”
Section: Introductionmentioning
confidence: 99%